Characterizing Sleep Differences in Children With and Without Sensory Sensitivities - Hartman, Amy G.; McKendry, Sarah; Soehner, Adriane; Bodison, Stefanie; Akcakaya, Murat; DeAlmeida, Dilhari; Bendixen, Roxanna (Frontiers in Psychology, 2022)
Objectives: Individuals register and react to daily sensory stimuli differently, which influences participation in occupations. Sleep is a foundational nightly occupation that impacts overall health and development in children. Emerging research suggests that certain sensory processing patterns, specifically sensory sensitivities, may have a negative impact on sleep health in children. In this study, we aimed to (i) characterize sleep in children with and without sensory sensitivities and (ii) examine the relationship between sensory processing patterns (using the Sensory Profile-2) and sleep using validated parent- and child-reported questionnaires. We hypothesized that children with sensory sensitivities will exhibit more difficulties with sleep. Methods: We recruited 22 children (ages 6-10) with sensory sensitivities (SS) and 33 children without sensory sensitivities (NSS) to complete validated sleep and sensory processing questionnaires: the Children’s Sleep Habits Questionnaire, Sleep Self-Report, and Sensory Profile-2. Results: Children with SS had significantly more sleep behaviors reported by both parents (p<.001, g=1.11) and children (p<.001, g=1.17) compared to children with NSS. Specifically, children with SS had higher frequencies of sleep anxiety (p=.004, g=0.79), bedtime resistance (p=.001, g=0.83), and sleep onset delay (p=.003, g=0.95). Spearman’s ρ correlations indicated significant positive correlations between parent- and child-reported sleep. Children with SS showed a larger association and greater variability between sleep and sensory processing compared to their peers. Significant positive correlations between parent-reported sleep behaviors and sensory sensitive and avoiding patterns were identified for both children with SS and NSS. Child-reported sleep behaviors were most strongly associated with sensitive and avoiding patterns for children with NSS and seeking patterns for children with SS. Conclusions: We present evidence that sleep is impacted for children with SS to a greater extent than children with NSS. We also identified that a child’s sensory processing pattern may be an important contributor to sleep problems in children with and without sensory sensitivities. Sleep concerns should be addressed within routine care for children with sensory sensitivities. Future studies will inform specific sleep intervention targets most salient for children with SS and other sensory processing patterns.